Booster Effect of a Natural Extract of Polypodium leucotomos (Fernblock®) That Improves the UV Barrier Function and Immune Protection Capability of Sunscreen Formulations - Aguilera, Jose; Vicente-Manzanares, Miguel; de Gálvez, María Victoria; Herrera-Ceballos, Enrique; Rodríguez-Luna, Azahara; González, Salvador (Frontiers in Medicine, 2021)
Background: Novel approaches to photoprotection must go beyond classical MED measurements, as discoveries on the effect of UV radiation on skin paints a more complex and multi-pronged scenario with multitude of skin cell types involved. Of these, photoimmunoprotection emerges as a crucial factor that protects against skin cancer and photoaging. A novel immune parameter is enabled by the precise knowledge of the wavelength and dose of solar radiation that induces photoimmunosupression. Natural substances, that can play different roles in photoprotection as antioxidant, immune regulation, DNA protection as well as its possible ability as sunscreen are the new goals in cosmetic industry. Objective: To analyze the effect of a specific natural extract from Polypodium leucotomos (PLE, Fernblock®), as part of topical sunscreen formulations to protect from photoimmunosuppression, as well as other deleterious biological effects of UV radiation. Methods: The possible sunscreen effect of PLE was analyzed by including 1% (w/w) PLE in four different galenic formulations containing different combinations of UVB and UVA organic and mineral filters. In vitro sun protection factor (SPF), UVA protection factor (UVA-PF), contact hypersensitivity factor (CHS) and human immunoprotection factor (HIF) were estimated following ISO 24443:2012 for in vitro determination. Results: PLE-containing formulations significantly reduced UV radiation reaching to skin. Combination of UVB and UVA filters with PLE increased SPF and UVAPF significantly. PLE also increased UV immune protection, by elevating the contact hypersensitivity factor and the human immunoprotective factor of the sunscreen formulations. Conclusion: This study confirms the double role of PLE in photoprotection. Together to the biological activity shown in previous works, the UV absorption properties of PLE confers a booster effect when it is supplemented in topical sunscreens increasing the protection not only at level of erythema and permanent pigment darkening but also against two photoimmunoprotection factors.